Analysis of Learning Strategies in the History of Islamic Civilization to Enhance Students Cognitive and Critical Thinking Skills - Hakim, Nurul; Zulhannan, Zulhannan; Wulandari, Heny (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
The study of History of Islamic Civilization is often understood as a subject that only teaches students to know and understand events or information from the past. However, the nature of this subject requires relevance to the context of students' lives today. In response to this, MTs Al-Ma'arif Suka Agung and MTs Mathla'ul Anwar Napal have sought to address this issue by developing a learning approach that goes beyond cognitive skills to focus on critical thinking. This study aims to analyze the efforts made by both madrasahs. The study employs a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. Efforts to enhance cognitive abilities and critical thinking skills begin with the planning phase of instruction, such as developing lesson plans and instructional materials that provide opportunities for students to engage in critical thinking. Instructional implementation employs various strategies and interactive media, such as discussions, presentations, and visual aids. Assessment is carried out formatively and summatively, covering cognitive, affective, and psychomotor aspects, and is used as a basis for improving learning. In general, the strategies applied are able to encourage active student participation and improve their understanding of Islamic history.